2003
DOI: 10.1242/jcs.00246
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial and nucleocytoplasmic targeting of O-linked GlcNAc transferase

Abstract: O-linked GlcNAc transferase (OGT) mediates a novel glycan-dependent signaling pathway, but the intracellular targeting of OGT is poorly understood. We examined the localization of OGT by immunofluorescence microscopy, subcellular fractionation and immunoblotting using highly specific affinity-purified antisera. In addition to the expected nuclear localization,we found that OGT was highly concentrated in mitochondria. Since the mitochondrial OGT (103 kDa) was smaller than OGT found in other compartments(116 kDa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
154
1
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 180 publications
(163 citation statements)
references
References 36 publications
(48 reference statements)
6
154
1
2
Order By: Relevance
“…O-GlcNAc is added by the enzyme OGT to serine and threonine of target proteins in the cytoplasm, nucleus, and mitochondrion (27,28). The single mammalian OGT gene is located on the human X chromosome near the Xist locus and encodes multiple alternatively spliced isoforms of OGT targeted to these different intracellular locations (27,28 isoforms are termed mOGT (mitochondrial OGT), ncOGT (nucleocytoplasmic OGT), and sOGT (short OGT) (Fig.…”
Section: The Enzymes Of O-glcnac Cyclingmentioning
confidence: 99%
See 1 more Smart Citation
“…O-GlcNAc is added by the enzyme OGT to serine and threonine of target proteins in the cytoplasm, nucleus, and mitochondrion (27,28). The single mammalian OGT gene is located on the human X chromosome near the Xist locus and encodes multiple alternatively spliced isoforms of OGT targeted to these different intracellular locations (27,28 isoforms are termed mOGT (mitochondrial OGT), ncOGT (nucleocytoplasmic OGT), and sOGT (short OGT) (Fig.…”
Section: The Enzymes Of O-glcnac Cyclingmentioning
confidence: 99%
“…1B). The mOGT isoform is targeted to the mitochondrial matrix and is proapoptotic (28,29). The sOGT isoform, present in the nucleus and cytoplasm, is antiapoptotic (28,30) and may inhibit the action of the other isoforms (29,31).…”
Section: The Enzymes Of O-glcnac Cyclingmentioning
confidence: 99%
“…Unlike many other glycosyltransferases, OGT is a soluble protein that is predominantly localized to the nucleus, mitochondria, and cytoplasm of all tissues studied thus far (Kreppel et al 1997;Haltiwanger et al 1992;Lubas et al 1997;Love et al 2003;Hanover et al 2003). Two functional domains characterize OGT: an N-terminal tetratricopeptide repeat (TPR domain) and a C-terminal catalytic domain belonging to the glycogen phosphorylase superfamily (Kreppel et al 1997;Lubas et al 1997;Wrabl and Grishin 2001).…”
Section: O-glcnac Transferasementioning
confidence: 99%
“…The gene for OGT maps to Xq13 on the mammalian X chromosome and encodes three well-characterized variants: short OGT, mitochondrial OGT (mOGT), and nuclear/cytoplasmic OGT (Kreppel et al 1997;Lubas et al 1997;Love et al 2003;Hanover et al 2003). mOGT has an alternative mitochondrial targeting sequence on its N-terminus.…”
Section: O-glcnac Transferasementioning
confidence: 99%
“…Impaired content or activity of enzymes related to mitochondrial function has been reported in STZ-or HFD-induced diabetic animal models [20][21][22][23]. Following the observation of OGT localisation to the mitochondria by Love et al [24], the presence of OGA was recently reported in cardiac mitochondria in rats [25]. Despite a recently identified association between OGA-mediated O-GlcNAcylation and diabetes progression [25,26], there have been no reports of the effects of OGA activity on mitochondrial regulation.…”
Section: Introductionmentioning
confidence: 99%